2013
DOI: 10.1080/02687038.2013.812779
|View full text |Cite
|
Sign up to set email alerts
|

Neural basis of action understanding: Evidence from sign language aphasia

Abstract: Background The neural basis of action understanding is a hotly debated issue. The mirror neuron account holds that motor simulation in fronto-parietal circuits is critical to action understanding including speech comprehension, while others emphasize the ventral stream in the temporal lobe. Evidence from speech strongly supports the ventral stream account, but on the other hand, evidence from manual gesture comprehension (e.g., in limb apraxia) has led to contradictory findings. Aims Here we present a lesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 42 publications
3
11
0
Order By: Relevance
“…The absence of PCS activation in experiment 1 cannot be attributed to a statistical lack of power as this study included five more subjects than experiment 2, where the PCS activation was present. The absence of a featural attention effect for manipulative actions in premotor cortex may suggest a more limited role for the premotor level for perceiving others actions, which is consistent with a number of studies (Buxbaum & Kalenine, 2010;Caramazza, Anzellotti, Strnad, & Lingnau, 2014;Negri et al, 2007;Rogalsky et al, 2013;Stasenko, Garcea, & Mahon, 2013).…”
Section: First Alternative: Little Task-specific Activation In Pm Asupporting
confidence: 89%
“…The absence of PCS activation in experiment 1 cannot be attributed to a statistical lack of power as this study included five more subjects than experiment 2, where the PCS activation was present. The absence of a featural attention effect for manipulative actions in premotor cortex may suggest a more limited role for the premotor level for perceiving others actions, which is consistent with a number of studies (Buxbaum & Kalenine, 2010;Caramazza, Anzellotti, Strnad, & Lingnau, 2014;Negri et al, 2007;Rogalsky et al, 2013;Stasenko, Garcea, & Mahon, 2013).…”
Section: First Alternative: Little Task-specific Activation In Pm Asupporting
confidence: 89%
“…We recently studied a group of deaf brain damaged signers and found that damage to the dorsal sensorimotor stream is not associated with sign comprehension deficits (Rogalsky et al, 2013), arguing that functional activation overlap found in the present experiment does not reflect sign or action understanding. Instead, sign comprehension deficits were associated with temporal lobe lesions, consistent with previous work (Hickok, Love-Geffen, & Klima, 2002).…”
Section: Discussionmentioning
confidence: 52%
“…We predicted that during sign observation, Deaf signers would show less sensorimotor system activity and less differentiation of sign types in the sensorimotor system, because of the possibility that for those individuals the task would involve language systems of the brain more robustly than sensorimotor systems. This hypothesis was based on prior work using a similar paradigm in a passive (non-imitative) task (Kubicek & Quandt, 2019), as well as other functional neuroimaging evidence (Corina & Knapp, 2006; Emmorey, Xu, Gannon, Goldin-Meadow, & Braun, 2010; Okada et al, 2016; Rogalsky et al, 2013). However, in opposition to our prediction, we found no significant differences in overall alpha/beta ERD between the two groups while participants were observing the signs.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have asked whether deaf signers, due to their extensive use of the hands and body for language, may show increases in mirroring activity when perceiving sign language. However, some sign language researchers determine that these processes have little to no role in in the higher-level neural and cognitive processing of sign languages (Corina & Knapp, 2006; Emmorey, Xu, Gannon, Goldin-Meadow, & Braun, 2010; Okada et al, 2016; Rogalsky et al, 2013). Several reports found no evidence to support the involvement of mirroring during sign perception (Rogalsky et al, 2013), and in fact generally suggested that signers recruit less of the sensorimotor system during sign perception, possibly because they are relying more on linguistic processing (Möttönen, Farmer, & Watkins, 2016).…”
Section: Mirroring Experience and Signmentioning
confidence: 99%
See 1 more Smart Citation